2013
DOI: 10.1534/genetics.113.152561
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Incipient Speciation in Arabidopsis lyrata from Patterns of Transmission Ratio Distortion

Abstract: Our understanding of the development of intrinsic reproductive isolation is still largely based on theoretical models and thorough empirical studies on a small number of species. Theory suggests that reproductive isolation develops through accumulation of epistatic genic incompatibilities, also known as Bateson-Dobzhansky-Muller (BDM) incompatibilities. We can detect these from marker transmission ratio distortion (TRD) in hybrid progenies of crosses between species or populations, where TRD is expected to res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 62 publications
2
52
0
Order By: Relevance
“…Kubo et al (2008) showed that hybrid male sterility is caused by epistasis between two novel genes, S24 and S35, on rice chromosomes 5 and 1. Similar results have also been found in Drosophila (Chang and Noor, 2010), alfalfa (Li et al, 2011), rice (Xie and Chen, 2012;Yang et al, 2012) and Arabidopsis lyrata (Leppälä et al, 2013). Thus, the Dobzhansky-Muller model, in which hybrid inviability is assumed to be caused by epistasis (Dobzhansky, 1936;Muller, 1942), has been widely accepted.…”
Section: Introductionsupporting
confidence: 68%
“…Kubo et al (2008) showed that hybrid male sterility is caused by epistasis between two novel genes, S24 and S35, on rice chromosomes 5 and 1. Similar results have also been found in Drosophila (Chang and Noor, 2010), alfalfa (Li et al, 2011), rice (Xie and Chen, 2012;Yang et al, 2012) and Arabidopsis lyrata (Leppälä et al, 2013). Thus, the Dobzhansky-Muller model, in which hybrid inviability is assumed to be caused by epistasis (Dobzhansky, 1936;Muller, 1942), has been widely accepted.…”
Section: Introductionsupporting
confidence: 68%
“…Gamete killers are also found in wild species, as in the interspecific cross between Mimulus guttatus and M. nasutus (Fishman and Saunders 2008), and, at the intraspecific level, in some populations of the dioecious Silene latifolia (Taylor and Ingvarsson 2003). Recently, several single-locus gametic transmission distorters were reported in interpopulation crosses of the A. thaliana relative A. lyrata, most of which affect pollen, although the causes of segregation distortion remain to be elucidated (Leppala et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Asymmetrical reproductive isolation probably involves cytoplasmic factors [42]. Accordingly, nucleocytoplasmic incopatibilities involving specific nuclear and cytoplasmic genes [45,46] have already been reported in wheats [47], but their predominant role was rejected in wild wheat, as the viability of F 1 hybrids should have been restored through the reorganization of specific nuclear loci of mostly paternal origin [9,15]. In stark contrast, the 38 surveyed hybrids revealed high levels of genome-wide restructuring and methylation changes, supporting that reorganization of interspersed sequences was necessary to produce viable hybrids.…”
Section: Discussion (A) Patterns Of Reproductive Isolation Between Wimentioning
confidence: 99%